Pemertahanan Identitas Bugis-Bajo Di Desa Sumberkima, Gerokgak, Buleleng, Bali Dan Potensinya Sebagai Sumber Belajar Sejarah - Andi Firdausi Hairul Izul Haj; I Made Pageh; Tuty Maryati (Universitas Pendidikan Ganesha, 2024)
The Bugis-Bajo on the coast of Sumberkima Village are interesting to study because tribes that are not native to the area are able to maintain their identity from the various existing tribes. The aims of this study were to: (1) Describe the background to the existence of the Bugis Bajo tribe in Sumberkima Village; (2) Describe the elements of identity that are still maintained by the Bugis Bajo in Sumberkima Village; (3) Describe aspects of the maintenance of Bugis Bajo identity in Sumberkima Village, which have the potential as a source of learning history. The method used in this study is a qualitative descriptive method with the following stages: (1) Determining the research location; (2) Determination of informants. Using purposive and snowball techniques; (3) Data collection techniques. includes observation, interview, and document study; (4) Data validation techniques, namely data triangulation and data analysis techniques. The results of this research are a description of the Background of the Existence of the Bugis-Bajo Tribe in Sumberkima Village, The identities that are still maintained by the Bugis-Bajo in Sumberkima Village include: Bajo Language, Stage Houses, Hereditary knowledge systems, special food, and Traditions . Aspects of Maintaining Bugis Bajo Identity in Sumberkima Village that Have Potential as a Source for Learning History include: historical aspects and socio-cultural aspects. Keywords: Defense, Identity, Ethnicity, Historical Learning Resources.